Climate Change in Your Backyard: When Climate is Proximate, People Become Activists - Sparks, Aaron C. (Frontiers in Political Science, 2021)
Scientific warnings about climate change continue as climate disasters strike all around the world. There is increasing public support for climate mitigation policies, and major mass protests shed light on the issue. How does climate change impact increase climate activism? I build on a conventional understanding of activism by adding the insight of construal level theory. When climate change is experienced more directly, people are more likely to act because they care more and can link concern to specific actions. Among a sample of Californians (MTurk; n=604) as climate was perceived as more proximate, respondents were more likely to take action. A survey-experiment conducted using a US sample (MTurk; n=609) demonstrated that as issues becomes more psychologically proximate, respondents were more likely to take political action. These results suggest that organizers can activate proximity to mobilize supporters.